2021
DOI: 10.1016/j.ajem.2020.12.049
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-associated pancytopenia and typhlitis

Abstract: Neutropenic enterocolitis is also known as typhlitis, is characterized by severe inflammation in the bowel loops. It is often seen in immunosuppressed patients, and it has high morbidity and mortality. Although the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) primarily affects the respiratory system and causes COVID-19 (Coronavirus Disease 2019), it may affect hematopoietic and gastrointestinal systems. Herein, we present a rare case of COVID-19-associated pancytopenia and typhlitis in a 60-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 10 publications
2
12
0
Order By: Relevance
“…The proposed mechanism of action in this case is a dysregulation of CD8 T‐cells via increased interferon‐gamma from monocytes. 19 , 20 Cases of aplastic anemia have been reported in individuals who developed COVID‐19, 21 but cases of pancytopenia have been reported in individuals who have received any of the available COVID‐19 vaccines including an mRNA vaccine. Currently, little to no information is known regarding the possible effects of the vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed mechanism of action in this case is a dysregulation of CD8 T‐cells via increased interferon‐gamma from monocytes. 19 , 20 Cases of aplastic anemia have been reported in individuals who developed COVID‐19, 21 but cases of pancytopenia have been reported in individuals who have received any of the available COVID‐19 vaccines including an mRNA vaccine. Currently, little to no information is known regarding the possible effects of the vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphopenia is a common laboratory finding in COVID-19 infected patients, and it usually correlates with disease severity; however, pancytopenia is a relatively rarer manifestation of COVID-19 infection. Most cases of SARS-Cov-2 induced pancytopenia are reported in immunocompromised patients [5,6,7]. Issa et al [5] reported persistent pancytopenia in an immunocompromised patient who had severe COVID-19 infection with cytokine storm.…”
Section: Discussionmentioning
confidence: 99%
“…Hershby et al [6] reported a similar patient with covid induced pancytopenia, but he had a milder clinical course, and bone marrow aspirate was negative for COVID-19 virus Pancytopenia also resolved as soon as symptoms of COVID-19 subsided. Ufuk et al [7] reported a "rare case" of pancytopenia and typhlitis (neutropenic enterocolitis) in a diabetic old age female case of COVID-19. Bridwell et al [8] presented a case of covid induced pancytopenia in an immunocompetent patient with no known risk factors, who eventually developed multiple organ failure [8].…”
Section: Discussionmentioning
confidence: 99%
“…Of course, similar infections are seen in patients with hematological malignancies, and such an overlap should be taken into account when encountering these patients. Typhlitis, a life-threatening necrotizing enterocolitis usually described in neutropenic patient, was also described in a patient without prior hematological malignancy with COVID-19-associated pancytopenia [ 53 ].…”
Section: Covid-19 Imaging Mimickers Of Common Hematological Findingsmentioning
confidence: 99%